Analyzing the Impact of Job Embeddedness, Work Motivation, and Bonus Mechanism on Employee Performance in the Context of Management Accounting - Mardjono, Enny Susilowati; Iskandariah, Yusuf (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
Management accounting uses performance data for strategic planning, control, and decision making. By understanding the relationship between Job Embeddedness, Work Motivation, and Bonus Mechanism, management can design measurement and reward systems that encourage continuous performance improvement. This study aims to analyze the effect of Work Attachment, Work Motivation, and Bonus Mechanism on Employee Performance. The sample in this study was all 150 employees of the Semarang Plaza Hotel. The sampling technique used a census. The data analysis method used was Multiple Linear Regression using the SPSS 25 application. The results obtained were that the variables Job Embeddedness and Work Motivation had no effect on Performance while the Bonus Mechanism Variable had a Positive effect on Employee Performance. Companies must optimize the existing compensation system by ensuring openness, fairness, and accuracy in providing bonuses, allowances, and other welfare facilities. Improving the quality of compensation can be a primary strategy in maintaining and increasing employee productivity.